Mycophenolate mofetil versus cyclophosphamide, in combination with prednisolone for lupus nephritis induction treatment: Findings from a prospective observational study - Rakhesh LR; Priya S Raju; Rajesh Wilson; Bindu Latha Nair R; Sanitha Kuriachan; Mahesh Kumar D; Jumi Jacob (Asian Journal of Medical Sciences, 2025)
Background: Lupus nephritis (LN) is a severe complication of systemic lupus erythematosus. Intravenous cyclophosphamide (CYC) is the standard induction therapy for proliferative LN, but it is associated with serious adverse effects such as sterility and bone marrow suppression. Mycophenolate mofetil (MMF) has emerged as a promising alternative, offering better renal outcomes and preserving fertility in women of childbearing age. Aims and Objectives: To compare the treatment outcomes and safety of MMF plus prednisolone versus CYC plus prednisolone in the induction treatment of LN. Materials and Methods: Patients with Class 3 and 4 LN who received either oral MMF (2 g/day) or CYC (0.75–1 g/m2) were included in the study. Remission rates and adverse events were measured as treatment outcomes. Results: The study found 81% remission in the MMF group compared to 76.4% in the CYC group (not statistically significant). Adverse effects in the MMF group included headache (52.4%), bone marrow toxicity (47.6%), back pain (42.9%), and gastrointestinal side effects (42.8%). The CYC group had higher rates of bone marrow toxicity (57.1%), respiratory infections (33.3%), and mucocutaneous infections (57.1%). Notably, alopecia (4.8% vs. 52.4%, P=0.001) and amenorrhea (4.8% vs. 28.6%, P=0.04) were significantly lower in the MMF group. Conclusion: The MMF-steroid regimen is highly effective for inducing remission in proliferative LN and offers a more favorable safety profile than the CYC-steroid regimen.